The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1513/pats.201201-009ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Therapeutics of Nrf2 as a Target for Prevention of Bacterial Exacerbations in COPD

Abstract: A growing body of evidence indicates that oxidative stress plays a central role in the progression of chronic obstructive pulmonary disease (COPD). Chronic oxidative stress caused by cigarette smoke generates damage-associated molecular patterns (DAMPs), such as oxidatively or nitrosatively modified proteins and extracellular matrix fragments, which induce abnormal airway inflammation by activating innate and adaptive immune responses. Furthermore, oxidative stress-induced histone deacetylase 2 (HDAC2) inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…It has also been reported that carbocisteine harbors other anti-inflammatory targets, such as nuclear factor-erythroid 2-related factor (Nrf2), which is a redox-sensitive transcription factor in COPD [37,38] that can be activated by TNF-α in certain cell lines [39] . Via the activation of Nrf2, carbocisteine attenuated inflammation in vivo after exposure to cigarette smoke following influenza virus infection [40] and alleviated cigarette smoke extract (CSE)-induced oxidative stress in vitro [5] .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that carbocisteine harbors other anti-inflammatory targets, such as nuclear factor-erythroid 2-related factor (Nrf2), which is a redox-sensitive transcription factor in COPD [37,38] that can be activated by TNF-α in certain cell lines [39] . Via the activation of Nrf2, carbocisteine attenuated inflammation in vivo after exposure to cigarette smoke following influenza virus infection [40] and alleviated cigarette smoke extract (CSE)-induced oxidative stress in vitro [5] .…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by a number of studies demonstrating that Nrf2 is essential for chemopreventive agents, such as sulforaphane and oltipraz, to block carcinogenesis and that Nrf2-deficient mice are more prone to chemical-induced cancer development [35]. Recent studies have demonstrated that Nrf2 also protects against chronic diseases such as cardiovascular disease, neurodegenerative diseases, and pulmonary injury [68]. However, the role of Nrf2 in human diseases is more complicated than originally thought.…”
Section: Introductionmentioning
confidence: 98%
“…Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a membrane of the cap ‘n' collar type of basic region leucine zipper factor family. Nrf2 is expressed broadly in tissue but is activated only in response to a range of oxidative stimuli [10]. Upon activation, Nrf2 translocates to the nucleus and binds to the antioxidant response element (ARE), which mediates the induction of a spectrum of cytoprotective proteins: the reduced form of nicotinamide adenine dinucleotide phosphate (NADPH):quinone oxidoreductase, heme oxygenase [11], glutathione reductase, superoxide dismutase (SOD) and catalase (CAT) [12].…”
Section: Introductionmentioning
confidence: 99%